2019
DOI: 10.1002/celc.201901402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chloride Oxidation on Local Electric Fields in Microelectrochemical Systems

Abstract: We recently reported that electrochemical oxidation of Cl− to neutral Cl2 decreases solution conductivity, thereby yielding a local electric field gradient. Here, we report detailed experimental results and simulations indicating that the situation is more complex than we originally thought. The key new findings are twofold. First, once generated, Cl2 rapidly reacts with water to form ionic species that increase, rather than decrease, solution conductivity near the anode. Second, the electrochemical potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…To ensure that there was no pressure-driven flow (PDF) in the absence of a driving voltage, the motion of the plastic microbeads was monitored. 33 Second, a driving voltage was applied across the channel length using a power supply (PWS 4721, Tektronix, Beaverton, OR) connected to Pt electrodes located on the floor of each reservoir. Third, a BPE of the desired length was formed by connecting two Pt microbands by an external jumper wire.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure that there was no pressure-driven flow (PDF) in the absence of a driving voltage, the motion of the plastic microbeads was monitored. 33 Second, a driving voltage was applied across the channel length using a power supply (PWS 4721, Tektronix, Beaverton, OR) connected to Pt electrodes located on the floor of each reservoir. Third, a BPE of the desired length was formed by connecting two Pt microbands by an external jumper wire.…”
Section: Methodsmentioning
confidence: 99%
“…170 However, a recent study has revealed that the instability of Cl 2 leads to rapid hydrolysis; this quenches the depletion zone, and prevents its use for seawater desalination. 171 The process of forming a depletion zone via a faradaic reaction can still be utilized in other separations where a more stable product can be formed, such as in a recent study on microplastic separations. Here, the neutralization of the TrisH + buffer to the stable TrisH species is used to form a depletion zone.…”
Section: Faradaic Depletion Zone Desalinationmentioning
confidence: 99%
“…First, as presently implemented, formation of an IDZ requires a buffered solution. Second, the large potential applied to the IDZ‐forming electrode may result in undesirable electrogenerated products that counteract IDZ formation . These shortcomings motivated us to explore other electrochemical methods for forming IDZs.…”
Section: Introductionmentioning
confidence: 99%